The issue of creation of AL-Muatazala and AL-Shaira - حسن منديل حسن العكيلي نبراس حسين مهاوش (College of Education for Women, 2019)
words of God the Quranic text , is genera words have many faces and connotations a ccording to references, cutures and Ages.That the Quranic text is fixed , But the connotations are moveable the scientists agreed about the miracle of the Qurantic text , But they differd of the Position of miracLe including the muatazala and Al- Ashaira who have adopted the idea of sytem and miracle of linguistic . Most of them were lingustics, grammerians and writers as: AL- Jahith, AL- Faraa Abivbeida , Ibn kutaba , AL -Rumani , AL -katabi , AL- Bakilaai , AL- Gargani and Others. They also differed in what the words of Allaah mean . Is the Quranic text creature or updated ,it is the issue that exhausted the effort.of muslim scientists though its imbortance and feasibility does not rais to the wide dispute which witnessed and the great sacrifices pressed to it that many scientists were its vichm . Our search deals with the semantic thinking of islamic philosphical of what the word of Alaah for islamic groups especaally with the muatazala and AL- shaira because they are the most famous islamic phiosophical groups in Quran. It includes three section as wellas pre-section the pre-section : privacy of the words of Alaah.-the first section : the subjects of speech and say in the Holly Quran -the second section: Almuatazlas opinion in the words of Alaah - the third section : Al-Ashairas opinion in the words of Alaah.